2012
DOI: 10.1002/cam4.41
|View full text |Cite
|
Sign up to set email alerts
|

Individual transcriptional activity of estrogen receptors in primary breast cancer and its clinical significance

Abstract: To predict the efficacy of hormonal therapy at the individual-level, immunohistochemical methods are used to analyze expression of classical molecular biomarkers such as estrogen receptor (ER), progesterone receptor (PgR), and HER2. However, the current diagnostic standard is not perfect for the individualization of diverse cases. Therefore, establishment of more accurate diagnostics is required. Previously, we established a novel method that enables analysis of ER transcriptional activation potential in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Furthermore, RvD2 concentration dependently increased ERE-SEAP transcriptional activity in ER-positive breast tumor cell lines (MCF-7, T47D, BT474) and in an ovarian tumor cell line (SKOV3). The enhancement of ERE transactivation was shown to have pathophysiological relevance, as it was paralleled by upregulation of GREB1 and PGR mRNA levels, well characterized ERE-containing estrogen-inducible genes (Deschênes et al, 2007;Gohno et al, 2012). The specificity of this phenomenon was confirmed by the observation that the RvD2 precursor docosahexaenoic acid did not have any impact on MDA-MB-231 and MCF-7 cell proliferation or ERE transactivation (data not shown).…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, RvD2 concentration dependently increased ERE-SEAP transcriptional activity in ER-positive breast tumor cell lines (MCF-7, T47D, BT474) and in an ovarian tumor cell line (SKOV3). The enhancement of ERE transactivation was shown to have pathophysiological relevance, as it was paralleled by upregulation of GREB1 and PGR mRNA levels, well characterized ERE-containing estrogen-inducible genes (Deschênes et al, 2007;Gohno et al, 2012). The specificity of this phenomenon was confirmed by the observation that the RvD2 precursor docosahexaenoic acid did not have any impact on MDA-MB-231 and MCF-7 cell proliferation or ERE transactivation (data not shown).…”
Section: Discussionmentioning
confidence: 82%
“…Comparison of IRS of PGRMC1 and pPGRMC1 with IRS of ERα, PR, total ERβ, Ki-67 and HER2/neu revealed a significant correlation of PGRMC1 and pPGRMC1 expression solely with ERβ expression. Interestingly, most clinical studies found that high expression of ERβ-like proteins is associated with a better clinical outcome although some studies do suggest otherwise [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of an adenovirus vector carrying an estrogen-response element-green fluorescent protein gene (Ad-ERE-GFP) was used to evaluate the level of ER activity. The methodology of this assay has been previously described in detail [16, 17]. Briefly, fresh tumor samples isolated through core needle biopsy were collected.…”
Section: Methodsmentioning
confidence: 99%